2007
DOI: 10.1186/1471-213x-7-56
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of neural crest derivatives in the Xenopustadpole tail

Abstract: Background: After amputation of the Xenopus tadpole tail, a functionally competent new tail is regenerated. It contains spinal cord, notochord and muscle, each of which has previously been shown to derive from the corresponding tissue in the stump. The regeneration of the neural crest derivatives has not previously been examined and is described in this paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 58 publications
(61 reference statements)
2
56
0
Order By: Relevance
“…The completeness of PNS regeneration seems to be a unique feature of the axolotl system. Similar tail amputation experiments carried out in Xenopus tadpoles revealed the lack of defined DRG regeneration (14), perhaps because of deficient expression of various embryonic signaling factors in the frog compared with the axolotl (21).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…The completeness of PNS regeneration seems to be a unique feature of the axolotl system. Similar tail amputation experiments carried out in Xenopus tadpoles revealed the lack of defined DRG regeneration (14), perhaps because of deficient expression of various embryonic signaling factors in the frog compared with the axolotl (21).…”
Section: Discussionmentioning
confidence: 59%
“…It was shown recently that, during development, melanocytes, another neural crest derivative, arise from precursors residing in peripheral nerve fibers (13). Furthermore, in Xenopus, studies of neural crest-ablated tadpoles showed that the melanophores regenerate from preexisting unpigmented melanophore precursors in the skin adjacent to the amputation site (14). This mechanism is similar to that described for the zebrafish fin regeneration, in which melanoblasts in the skin generate the new melanophores in the regenerated fin (15).…”
Section: Spinal Cord Transplantations Suggest That Newly Formed Drg Canmentioning
confidence: 61%
“…Spinal ganglia (dorsal root ganglia), normally present as organized collections of neural crest derived sensory neurons on each somite, are almost entirely missing, and the normal segmented pattern of the spinal nerves is not reestablished in the regenerate (Filoni and Bosco, 1981). Other neural crest cell derivatives such as melanophores (pigment cells) are regenerated normally, albeit through a different mechanism (Lin et al, 2007). During development, the neural crest cells arise from a region between the neural plate and flanking epidermis, and they migrate away after the neural plate folds up into a tube to form the spinal cord.…”
Section: Box 1: Does the Tail Regenerate Via A Blastema Or Regeneratimentioning
confidence: 99%
“…During development, the neural crest cells arise from a region between the neural plate and flanking epidermis, and they migrate away after the neural plate folds up into a tube to form the spinal cord. This interaction between epidermal cells and neural plate cells does not occur during regeneration, and the replacement melanophores do not originate from regenerated neural crest but from existing precursors located in the blastema and presumably recruited from fin tissue near the stump (Lin et al, 2007).…”
Section: Box 1: Does the Tail Regenerate Via A Blastema Or Regeneratimentioning
confidence: 99%
“…In short, the selection of these neuronal and glial markers meet the following criteria: 1) they are useful tools to analyze the axonal regrowth process in regeneration models of both the central and peripheral nervous systems; 2) they are highly conserved molecules among vertebrates; and 3) the available antibodies also stain specifically in different vertebrates, particularly in nonmammalian species: chicken (Bergmann et al, 2000;Fischer, 2005;Soukkarieh et al, 2007), lizards (Rodger et al, 2006;Santos et al, 2008), salamanders, frogs (Yang et al, 2002;Lin et al, 2007), and fish (Good, 1995). Thus, a comparison among the available regeneration models of the nervous system is easily made.…”
mentioning
confidence: 99%